(3ahGFO ddTQja GdeQJVis - (3YHjO Gddg Hf eMeO GdgGTej GdMSjfj GdaQZGfj HQgGf GdOjf, GdeYQha HGdYHQj , hjfYJ HGdTQja GdeQJVj,J (B743 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3hHYO agPg ahGFO ef cdGe GdeQJVi Yde GdgOi SFd GdeQJVi abjd Cf Gddg Ndb GdNdb s
(3BNQgG (B:s
(3hbhdg(B: "(3haGcgI eeG jJNjQhf(B" (3UQjM ai Cfge oeNJGQhf aEPf KHJ Gfge ZjQ eVWQjf Edi CaYGdge s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B136s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(2/433) s
Keywords: (3GdJhMjO hGdedd hGdfMds